The Relationship Between Knowledge and Preparedness with Anxiety Levels Among Traders on the South Coast Against Megathrust Disasters - Rangga Rendiyanto; Riris Risca Megawati; Bagus Ananta Tanujiarso (LP3M Universitas Muhammadiyah Tasikmalaya, 2026)
A megathrust disaster is a geological event caused by the movement of tectonic plates, leading to potentially severe damage to infrastructure due to immense pressure accumulated in the subduction zone from the friction between two plates. This disaster caused 3 people to die, 29 were injured, 151 people were displaced, out of 101,500 people who suffered. The impacts of megathrust earthquakes affect various aspects of life and the environment, including individuals’ knowledge and preparedness. Coastal traders, whose locations are often in close proximity to the coastline, are at high risk of losing their livelihoods and assets, which may increase their anxiety levels. This study aims to examine the relationship between knowledge and preparedness with the anxiety levels of coastal traders in the southern coastal region in the context of megathrust disasters. A quantitative research method with a cross-sectional design was employed. Data were collected using questionnaires measuring knowledge, preparedness, and anxiety levels. The study involved 71 respondents selected through purposive sampling. The results showed no significant relationship between knowledge and anxiety levels (p = 0.653; r = 0,054). However, a significant relationship was found between preparedness and anxiety levels (p = 0.049, r = 0,234). It is recommended that future studies explore the effectiveness of disaster education or training interventions in reducing anxiety levels among traders in high-risk coastal areas.